The identification and validation of novel aptamers for the diagnosis of oligodendroglioma. (31st January 2018) - Coxon, Catherine; Alder, Jane; Shaw, Lisa; Lawrence, Clare
Abstract: Oligodendroglioma account for nearly 12% of brain tumours (Jain et al., 2017). In the United Kingdom, 0.4 people per 100 000 per year are newly diagnosed with oligodendroglioma (Crocetti et al., 2012). Early diagnosis and treatment of oligodendroglioma is essential as patients given the appropriate chemotherapy survive on average nearly 8 years longer than patients given radiotherapy alone (Cairncross et al., 2014). Aptamers are short, single-stranded nucleotide sequences (DNA or RNA) that uniquely fold to form specific recognition molecules that selectively bind to a molecular target. Aptamers against targets are generated using a process called systematic evolution of ligands by exponential enrichment (SELEX). Since 2002, a number of aptamers have been identified that can selectively identify cancerous cells. These aptamers have been used both diagnostically and therapeutically against a range of different cancers, however, there are currently no aptamers specific to glioma tissue. This first part of this project was to find aptamers specific to the grade IV glioblastoma cell line U87MG. Previous studies have found aptamers that were able to distinguish U87MG from non-malignant cell lines but showed good binding to most highly tumorigenic cell lines (Cerchia et al., 2009; Aptekar et al., 2015). To ensure that highly specific aptamers were identified, a large number of negative controls were utilised, and two variants of the SELEX process were undertaken to ascertain whether the negative controls had to be selected against individually or if they could be pooled. Patient brain tumour samples will be obtained from the Brain Tumour North West (BTNW) tissue bank and aptamers specific to oligodendroglioma will be selected. These aptamers will be used to screen patient samples to determine if they can identify oligodendroglioma tissue and be of use diagnostically, therapeutically and as a drug delivery tool.